Analysis of Triple Helix-Based Collaborative Governance in the Implementation of the New Student Admission Policy (PPDB) at SD Negeri 20 Palembang: Analisis Collaborative Governance Berbasis Triple Helix dalam Implementasi Kebijakan Penerimaan Peserta Didik Baru (PPDB) di SD Negeri 20 Palembang - Een Endasari; Rizki Yolanda; Muslim; Mawaddah (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study analyzes the implementation of the New Student Admission Policy (PPDB) at SD Negeri 20 Palembang using a collaborative governance approach based on the Triple Helix model, emphasizing interaction between government, academia, and society. Design/Methodology/Approach: A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation involving the Palembang City Education Office, school actors, and parents as informants. Findings: Although the PPDB policy was implemented according to regulations, its effectiveness remains low. The online registration system failed due to limited digital literacy and community access. Collaboration among actors exists but remains administrative, lacking synergy and innovation, resulting in suboptimal policy outcomes. Practical Implication: The government must strengthen its role as both regulator and facilitator through intensive socialization, technical assistance, and digital literacy training. Schools should serve as mentoring centers for parents navigating the online system. Supporting facilities such as internet access must be provided, and the PPDB policy should be made more flexible and adaptive to local social conditions to prevent digital access gaps. Originality/Value: This study contributes a novel analytical framework by integrating collaborative governance and the Triple Helix model in the context of local digital education policy. Unlike previous studies focused on technical aspects, this research uncovers structural policy failure through institutional asymmetry and pseudo-collaboration. It demonstrates that digital transformation in education requires not only technological readiness but also social readiness and equal collaborative capacity among all stakeholders. Paper type: Research Paper